The global role of Lrp in Vibrio alginolyticus and its response to diverse physicochemical factors - Su, Wenxiao; Deng, Yiqin; Zang, Shujun; Gao, Si’ao; Feng, Juan (Frontiers in Marine Science, 2022)
Leucine-responsive regulatory protein (Lrp) is an essential transcriptional regulator in prokaryotes. However, the regulatory role of lrp in Vibrio alginolyticus has still not been studied in detail. In this study, an lrp mutant strain was constructed to gain insight into the role of lrp in Vibrio alginolyticus. The absence of lrp significantly enhances swarming motility, biofilm formation, extracellular protease secretion activity, and tolerance to copper ions. The cumulative mortality of zebrafish (Danio rerio) challenged by intraperitoneal injection against the lrp mutant strain reached 68.89%, significantly higher than the 40.00% suffered by fish injected with the wild-type strain. The expression levels of lrp decreased gradually with increasing culture time under the influence of various physicochemical factors. The expression level of lrp was significantly increased after two hours of culture at pH 5, 22°C, 5% NaCl, the presence of 1 mM Cu2+, 1/4/7 mM ferric citrate, 0.1 mg/L NaNO3, and 0.1 mg/L KH2PO4. The mRNA level of lrp decreased significantly after six hours of culture at 37°C, 1% and 5% NaCl, and the presence of 1/7 mM ferric citrate, 0.1/5 mg/L NaNO3, and 0.1/0.5/2.0 mg/L KH2PO4. The expression of lrp increased after ten hours of culture at pH 5/9, 22°C, 1% NaCl, and the presence of 1 mM Cu2+, 7 mM ferric citrate, 5 mg/L NaNO3, and 0.1 mg/L KH2PO4. Overall, this study indicates that lrp negatively controls the virulence of V. alginolyticus, probably by reducing its swarming motility, biofilm formation, extracellular protease secretion activity, and tolerance to copper ions, and that the expression of lrp is affected by numerous physicochemical factors, and is especially up-regulated after 2 hours of culture in bacterial growth.